(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
The current study investigates the competency-based extent of the Algerian English language Baccalaureate test. The BAC test was evaluated against a set of criteria derived from the review of the expert literature. Results indicate that only 30 % of the test questions can be considered competency-driven, but faulty in terms of competency-focused assessment principles such as complexity of the task, meaningfulness of the task, multiplicity of task instructions, and diversity of scoring standards. The other 70 % of the test questions are focused on the measurement of resources, with 10 % devoted to knowledge and 60 % to skills/abilities measurement. Nevertheless, of this large sum of percentage devoted to the assessment of resources, only 10 % percent is justified from a competency-based theory. Keywords: Assessment of complex situations, Assessment of resources, BAC testing, competency-based approach, Competency- Assessment, pedagogy of integration, Skills-assessment.